A biophysiological framework exploring factors affecting speech and swallowing in clinical populations: focus on individuals with Down syndrome - Madhavan, Aarthi; Lam, Larissa; Etter, Nicole M.; Wilkinson, Krista M. (Frontiers in Psychology, 2023)
Speech and swallowing are complex sensorimotor behaviors accomplished using shared vocal tract anatomy. Efficient swallowing and accurate speech require a coordinated interplay between multiple streams of sensory feedback and skilled motor behaviors. Due to the shared anatomy, speech and swallowing are often both impacted in individuals with various neurogenic and developmental diseases, disorders, or injuries. In this review paper, we present an integrated biophysiological framework for modeling how sensory and motor changes alter functional oropharyngeal behaviors of speech and swallowing, as well as the potential downstream effects to the related areas of language and literacy. We discuss this framework with specific reference to individuals with Down syndrome (DS). Individuals with DS experience known craniofacial anomalies that impact their oropharyngeal somatosensation and skilled motor output for functional oral-pharyngeal activities such as speech and swallowing. Given the increased risk of dysphagia and ‘silent’ aspiration in individuals with DS, it is likely somatosensory deficits are present as well. The purpose of this paper is to review the functional impact of structural and sensory alterations on skilled orofacial behaviors in DS as well as related skills in language and literacy development. We briefly discuss how the basis of this framework can be used to direct future research studies in swallowing, speech, and language and be applied to other clinical populations.